2005
DOI: 10.1117/1.2007987
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of functional brain activity with near-infrared diffusing-wave spectroscopy

Abstract: Abstract. We use near-infrared dynamic multiple scattering of light ͓diffusing-wave spectroscopy ͑DWS͔͒ to detect the activation of the somato-motor cortex in 11 right-handed volunteers performing a finger opposition task separately with their right and left hands. Temporal autocorrelation functions g ͑1͒ ͑r , ͒ of the scattered light field are measured during 100-s periods of motor task alternating with 100-s resting baseline periods. From an analysis of the experimental data with an analytical theory for g ͑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 52 publications
(57 reference statements)
6
160
0
Order By: Relevance
“…Previous studies using fNIRS confirmed results from traditional methods demonstrating functional oxygenation changes in response to simple motor activation tasks (Kleinschmidt et al, 1996, Maki et al, 1996, Franceschini et al, 2003, Koeneke et al, 2004, Li et al, 2005, Sato et al, 2007, Grefkes et al, 2008, Mackert et al, 2008, Shibuya et al, 2008. It is unknown, however, whether fNIRS can also detect changes in response to tasks with increasing complexity.…”
Section: Introductionmentioning
confidence: 69%
“…Previous studies using fNIRS confirmed results from traditional methods demonstrating functional oxygenation changes in response to simple motor activation tasks (Kleinschmidt et al, 1996, Maki et al, 1996, Franceschini et al, 2003, Koeneke et al, 2004, Li et al, 2005, Sato et al, 2007, Grefkes et al, 2008, Mackert et al, 2008, Shibuya et al, 2008. It is unknown, however, whether fNIRS can also detect changes in response to tasks with increasing complexity.…”
Section: Introductionmentioning
confidence: 69%
“…Both contra-and ipsilateral stimulations show enhanced cortical dynamics. We find that the contralateral response (approximately 39%) is stronger than the ipsilateral (20%) [13] …”
Section: Bmentioning
confidence: 70%
“…Output from the laser can be delivered to the tissue through a multimode optical fiber. Single-mode 23 (or few-mode 20,49 ) fibers should be used to collect photons from a single (or a few) speckle(s) emitted from the tissue surface. Fast photon-counting avalanche photodiodes (APDs) (e.g., SPCM-AQR-12, Perkin Elmer, CA) are generally used as detectors.…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
“…Endogenous tumor-to-normal contrasts available to NIRS include: tissue absorption; scattering; concentrations of oxy-, deoxy-, and total-hemoglobin, water and lipids; and blood oxygen saturation. [7][8][9][10][11][12][13][14][15] A relatively new dynamic NIR technique, namely diffuse correlation spectroscopy (DCS) 16,17 or diffuse wave spectroscopy (DWS), [18][19][20] has been developed which can directly measure the motions of red blood cells in biological tissues while also maintaining all the advantages of NIRS. DCS flow measurements are accomplished by monitoring speckle fluctuations of photons induced by the moving scatterers in tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation